2021
DOI: 10.3390/su131910771
|View full text |Cite
|
Sign up to set email alerts
|

Outbreaks of the Fall Armyworm (Spodoptera frugiperda), and Maize Production Constraints in Zambia with Special Emphasis on Coping Strategies

Abstract: The fall armyworm (FAW) (Spodoptera frugiperda J.E. Smith) is an invasive pest of maize, as well as other important cereals and vegetables, threatening food systems and biodiversity in Sub-Saharan Africa. This study aimed to assess the outbreaks of the FAW, farmers’ perceived production constraints, and coping strategies in maize production in Zambia. A participatory rural appraisal (PRA) study was conducted in two FAW-affected maize production districts in Zambia in 2017 and 2018. Data were collected using se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…constricted breeding pool of FAW resistant maize and improve elite but FAW susceptible maize genotypes. Moderate resistance to FAW in maize was also reported by Ni et al (2014) and Kasoma et al (2021). According to Womack et al (2018), many underlying genes whose effects are small confer partial resistance to FAW in maize.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…constricted breeding pool of FAW resistant maize and improve elite but FAW susceptible maize genotypes. Moderate resistance to FAW in maize was also reported by Ni et al (2014) and Kasoma et al (2021). According to Womack et al (2018), many underlying genes whose effects are small confer partial resistance to FAW in maize.…”
Section: Discussionmentioning
confidence: 85%
“…Consequently, breeding for resistance to FAW will benefit from heterotic grouping of parental lines. Kasoma et al (2021), in their study, found that nonadditive genetic effects were more important for GY under FAW infestation. Genotype x environment interaction was evident for most of the traits evaluated, including FAW resistance-associated traits, which indicates the importance of conducting multi-location trials to identify stable genotypes in contrasting environments (Abu et al, 2021).…”
Section: Discussionmentioning
confidence: 90%
“…However, in South Africa and neighbouring countries, many areas may be too cold for populations to persist (Early et al 2018;du Plessis et al 2018). The damage reported in at least some parts of Zimbabwe (Baudron et al 2019;Chimweta et al 2020;Tambo et al 2020a) and Zambia (Tambo et al 2020b;Kasoma et al 2021a) might therefore be due to immigrant populations.…”
Section: Worldwide Status and Geographic Spreadmentioning
confidence: 99%
“…Screening for FAW resistance in maize is ongoing (Kasoma et al 2021b). Several quantitative trait loci, localised on chromosome 9, have been found associated with resistance to FAW in maize (see Kasoma et al 2021a for a list and references) and are candidates for introgression into elite maize genotypes.…”
Section: Classical Resistance Selectionmentioning
confidence: 99%
“…In parallel, a number of literatures explore the control strategies used by farmers in some parts of Africa and their perception towards such management practices against FAW (Ahissou et al, 2022; Ansah et al, 2021; Caniço et al, 2021; Chimweta et al, 2020; Houngbo et al, 2020; Hruska, 2019; Kansiime et al, 2019; Kasoma et al, 2021; Kassie et al, 2020; Kumela et al, 2019; Tambo et al, 2019, 2021, 2022; Tambo, Day et al, 2020; Tambo, Kansiime et al, 2020). Although research has already been undertaken in Africa, information on indigenous practices is lacking in some African countries, especially in French‐speaking countries, such as DR Congo, Gabon, Senegal etc., yet farmers in these countries have been facing the FAW invasion since 2016 and indigenous knowledge, perceptions and management practices might be different depending on the situation in each country.…”
Section: Introductionmentioning
confidence: 99%